Advancing treatment options for chronic idiopathic constipation. (3rd March 2016) - Quigley, Eamonn M. M.; Neshatian, Leila
ABSTRACT: Introduction : Chronic constipation is a global problem affecting all ages and associated with considerable morbidity and significant financial burden for society. Though formerly defined on the basis of a single symptom, infrequent defecation; constipation is now viewed as a syndrome encompassing several complaints such as difficulty with defecation, a sense of incomplete evacuation, hard stools, abdominal discomfort and bloating. Areas covered : The expanded concept of constipation has inevitably led to a significant change in outcomes in clinical trials, as well as in patient expectations from new therapeutic interventions. The past decades have also witnessed a proliferation in therapeutic targets for new agents. Foremost among these have been novel prokinetics, a new category, prosecretory agents and innovative approaches such as inhibitors of bile salt transport. In contrast, relatively few effective therapies exist for the management of those anorectal and pelvic floor problems that result in difficult defecation. Expert opinion : Though constipation is a common and often troublesome disorder, many of those affected can resolve their symptoms with relatively simple measures. For those with more resistant symptoms a number of novel, effective and safe options now exist. Those with defecatory difficulty (anismus, pelvic floor dysfunction) continue to represent a significant management challenge.